Topical therapy of molluscum contagiosum as a comparative therapeutic study using 15% phenol in lactic acid, 5% tincture iodine and pricking alone - Khalifa E. Sharquie; Adil A. Noaimi; Ghassan A. Ibrahim; Ali S. Al-Husseiny (Our Dermatology Online, 2016)
Introduction: Molluscum contagiosum is a common viral infection of the skin, caused by poxvirus, commonly affects young children. Although there was no specific treatment for molluscum contagiosum virus, many therapeutic modalities were used with different response rates. Aims: To evaluate the effectiveness of topical 15% phenol in lactic acid, 5% tincture iodine and pricking alone through comparative treatments of molluscum contagiosum. Materials and Methods: This randomized, therapeutic, single, blinded, comparative study was conducted in the Department of Dermatology-Baghdad Teaching Hospital Baghdad, Iraq, during the period from October 2007 to October 2008. Seventy-five patients with molluscum contagiosum were included in this study. They were diagnosed on clinical bases. Patients with prior treatment in the last 2 weeks and patients who had inflamed lesions were excluded. Full history and physical examination were done for all Patients. The patients were divided into 3 equal groups according to the mode of therapy (25 patients for each group): Group 1 patients treated by pricking the lesions with orange stick dipped in 15% phenol in lactic acid. Group 2 patients treated by pricking the lesions with orange stick dipped in 5% tincture iodine. Group 3 patients treated by pricking with orange stick alone. The treatment sessions were done at the time of presentation and then every week until complete cure was achieved, but not more than three sessions. The patients were followed up after one month from the last session to record the clinical cure and any local or systemic side effects. Results: Seventy five patients with molluscum contagiosum, 43 (57%) males and 32 (43%) females with male to female ratio 1.3-1, their ages ranged from 2-35 years(median:6 years). The most common age groups affected were below 10 years; 57 (76%) patients. The most common affected body sites were the face and neck 58 (77.3%) patients. Atopic diseases like atopic dermatitis, allergic bronchitis were found in 17 (22.7%) patients. After 3 weeks of treatment, the response rates were as follows: Group 1: 23/25 (92%) patients cured completely, 2 (8%) patients failed to achieve complete clearing, p-value was highly significant <0.000001. Group 2: 22/25 (88%) patients completely cured, 3 (12%) patients not responded completely, p-value was highly significant < 0.000001. Group 3: 21/25 (84%) patients completely cured, 4 (16%) patients continue to develop new lesions, p-value was highly significant < 0.000001. When these groups compared with each other there was no statistically difference (p-value>0.05). Scars were not reported in any group. Conclusion: Pricking molluscum contagiosum lesions by orange stick alone is safe, cost effective, highly effective and stimulating mode of therapy. Still topical 15% phenol in lactic acid and 5% tincture iodine are new and effective modes of treatment.